Analysis of Financial Performance Reports on PT Energi Mega Persada for the Period 2015-2024 - Reky Naldo; Fadhil Fadlurrahman; Nurhana Dhea Parlina (PT FORMOSA CENDEKIA GLOBAL, 2025)
Indonesia, rich in natural resources, relies heavily on the oil and gas sector for state revenue and regional economic growth. PT Energi Mega Persada Tbk, an upstream oil and gas company listed on the Indonesia Stock Exchange, needs to present accurate financial reports to support decision making and maximize profits. This study analyzes the company's financial performance using liquidity, profitability, activity, and solvency ratios through a qualitative descriptive approach. Data is taken from the company's secondary financial statements. The analysis results show significant fluctuations, such as the lowest current ratio of 0.34 in 2018 and the highest of 1.13 in 2024, as well as the Debt to Asset Ratio which reached 107% in 2016-2017. Activity and profitability ratios show low efficiency and profitability. These findings highlight the ongoing financial challenges faced by the company, including liquidity pressures, high debt levels, and inefficient asset management.